Stereochemical assignment of fusiccocadiene from NMR shielding constants and vibrational circular dichroism spectroscopy. Issue 8 (30th May 2017) - Merten, Christian; Dirkmann, Michael; Schulz, Frank
Abstract: The absolute configuration (AC) of the common precursor of the fusicoccane family of terpenoids, fusicocca‐2, 10(14)‐diene (FCdiene), had only been deduced by a lengthy total synthesis, or indirectly from crystal structures of fusicoccin A. However, in particular the AC determinations based on downstream products of the terpene synthase intrinsically overlook potential epimerization reactions. In this contribution, we confirm the relative stereochemistry of FCdiene by comparison of experimental and predicted 13 C–NMR chemical shifts, and finally determine the absolute configuration from an analysis of its infrared and vibrational circular dichroism spectra. Abstract :